Pengembangan Media Pembelajaran Berbasis Multimedia Interaktif Menggunakan Macromedia Flash Pada Materi Aritmatika Sosial - Enggar Maulana Putri Qonita; Sri Rezeki; Aulia Sthephani; Nofriyandi (Jurnal Inovasi Pendidikan Matematika (JIPM), 2022)
Research and development include the development of Interactive Multimedia-Based Learning Media Using Macromedia Flash. This study aims to produce learning media that are tested valid. The data collection instrument in this study was a validation sheet. The data used to assess the validity of the learning media was obtained through a validation sheet with a Likert scale and a Guttman scale. The data analysis technique used is descriptive analysis. Validation data from 2 lecturers and 1 teacher. The study's results obtained the results of the validation of learning media, equal to 87.17%, with a very valid category. The study's results that Interactive Multimedia-Based Learning Media Using Macromedia Flash on Social Arithmetic Materials for Class VII were very valid.